Budaya Damai Mahasiswa di Yogyakarta - Eliasa, Eva Imania (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2017)
This study aims to identify the culture of peaceful student Yogyakarta, based on the background of gender, ethnicity and other aspects of the culture of peace. The research approach using quantitative descriptive type. The population of the research is the Yogyakarta State University student. The research sample using simple random sampling a number of 210 students. Number of samples 78 male students and 132 female students. Collecting data using questionnaires. Data were analyzed using descriptive test and chi square test different. The research result is a culture of peaceful student Yogyakarta State Universisitas including high category. Faculty and ethnic backgrounds have differences in culture of peaceful student. No gender differences in student culture of peace. Students were high in this aspect of the culture of peace is love, harmony, tolerance, compassion or pity, caring and sharing and interdepency, while the introduction of aspects of the lives of others and thank aspects including very high category.